1999
DOI: 10.1093/geront/39.6.658
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving as a Life Course Transition Among Older Husbands: A Prospective Study

Abstract: Guided primarily by transitions theory, this study examined changes over two points in time (approximately 5 years apart) in multiple life domains (i.e., household tasks, social life, marital relationship, and well-being) between two groups of husbands aged 60 and older, who indicated that their wives were not in need of care or assistance due to an illness or disability at the initial interview. The two groups included husbands who identified themselves as a provider of care at Time 2 (T2; i.e., they had tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
53
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 63 publications
1
53
1
Order By: Relevance
“…[29][30][31][32] The three essential stages of caregiving are (1) role acquisition, which is often an insidious process precipitated by onset of the illness and the care recipient's needs; (2) role enactment, which traditionally has been viewed as performance of role-related tasks within the home or in an institutional setting (e.g., a nursing home); and (3) role disengagement, which follows death and typically involves bereavement and recovery. According to this model, Each stage of caregiving presents distinctive sources of stress; offers some strategies for addressing these difficulties, at the same time as it precludes alternative options; utilizes various personal, social, and economic coping resources, while depleting others; and shapes the choices available in ensuing stages.…”
Section: Conceptual Framework: Family Caregiving Careermentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32] The three essential stages of caregiving are (1) role acquisition, which is often an insidious process precipitated by onset of the illness and the care recipient's needs; (2) role enactment, which traditionally has been viewed as performance of role-related tasks within the home or in an institutional setting (e.g., a nursing home); and (3) role disengagement, which follows death and typically involves bereavement and recovery. According to this model, Each stage of caregiving presents distinctive sources of stress; offers some strategies for addressing these difficulties, at the same time as it precludes alternative options; utilizes various personal, social, and economic coping resources, while depleting others; and shapes the choices available in ensuing stages.…”
Section: Conceptual Framework: Family Caregiving Careermentioning
confidence: 99%
“…31 An important concept within the caregiving career model involves the transitions that occur from one stage of caregiving to another and the transitional events that may occur within each stage. 31 Research on the experiences of family members caring for an older adult with cognitive or physical impairments has produced the most empirical data about these transitional events: (1) onset of the illness, precipitating the start of care in the role-acquisition stage; [32][33][34][35] (2) nursing home admission, precipitating institutional care in the role-enactment phase [35][36][37][38][39][40] ; and (3) the patient's death, precipitating bereavement in the role disengagement stage. 37,39,[41][42][43] Because these transitional events occurring between and within stages represent periods of rapid change, they are particularly challenging and important to under-stand.…”
Section: Conceptual Framework: Family Caregiving Careermentioning
confidence: 99%
“…Chang, Brecht, and Carter [13] found that occupying a larger number of roles was correlated with more hostility and anxiety. Research has tied caregiving to depression [5,14] and anxiety [12], suggesting the need to better understand and prevent these strains to improve outcome for caregivers and their care recipients.The present study was guided by Pearlin's Stress Process Model [15], and focused on three of its components: stressors, resources, and outcomes. Stressors are problems or negative events that threaten a person's ability to adapt and include eventful (single-event) or chronic stressors.…”
mentioning
confidence: 99%
“…Chang, Brecht, and Carter [13] found that occupying a larger number of roles was correlated with more hostility and anxiety. Research has tied caregiving to depression [5,14] and anxiety [12], suggesting the need to better understand and prevent these strains to improve outcome for caregivers and their care recipients.…”
mentioning
confidence: 99%
See 1 more Smart Citation